The relevance of psychological capital on individual's perceptions of performance, motivation, work-engagement and job-satisfaction - Barbosa, Ana Isabel Veloso (2017)
The concept of psychological capital (PsyCap) has been a great focus of interest and curiosity from academics and practitioners. The principal purpose of the present research is to study the relevance of PsyCap and its influence in employees’ attitudes, behaviors and performance. This investigation also aims to understand the importance of an authentic leader (leaders with power to influence their followers and to develop their capabilities) and the impact that the leader’s PsyCap may have on their followers’ dimensions (performance, motivation, work-engagement and job-satisfaction). Data was collected from both Linkedin and from a small company operating in the transportation sector, through a customized survey. The results support the literature showing that: (a) the individual psychological capital has an influence on individuals’ perceptions of performance, motivation, work-engagement and job-satisfaction; (b) the leaders’ PsyCap and the goodwill between the leader and followers may cause some positive impacts on followers’ perceptions of performance, motivation, work-engagement and job-satisfaction; and (c) the leaders’ psychological capital may affect the followers’ level of PsyCap.